Vitamin D Levels in Children During Winter and the Relationship Between Sunscreen and Sun Protection Behaviors - Burcu Tugrul; Hatice Gamze Demirdag; Aysin Hanli Sahin (Mattioli1885, 2023)
Introduction: Sunlight is the major source of vitamin D, thus, the use of sunscreens could result in vitamin D insufficiency or deficiency. Objective: We aimed to assess serum vitamin D levels in healthy children aged 0-18 years in the winter and determine the association between sunscreen use and sun protection behaviors on vitamin D status. Methods: The demographic data, clothing style, skin type, history of sunburn, history of visiting seaside towns in summer, sun protection behaviors including sunscreen use, wearing sunglasses and hats, and further detailed information about sunscreen use were recorded. Vitamin D status was assessed by measuring blood levels of 25(OH)D during winter. Results: Three hundred seventy-six children (172 boys and 204 girls) with a mean age of 128.38±56.39 months were enrolled. The mean serum level of 25(OH)D was 15.32±8.64 ng/mL. The mean values of vitamin D were associated with age, sex, traditional clothing style, having a sunburn history, and sunscreen use (p<0.05). Adolescents and girls had vitamin D deficiency and inadequacy more than younger children and boys (p<0.05). Sunscreen use in the adequacy group was lower than in the inadequacy and deficiency groups (p=0.001). There was no significant difference between vitamin D status according to the sunscreen details (SPF, product source, season, and body areas) (p>0.05). Conclusions: Sunscreen use appears to reduce vitamin D levels measured in winter. Children, especially girls and adolescents, should be exposed to sufficient sunlight to maintain normal serum vitamin D levels. Vitamin D supplementation should be given to children, especially during winter.